ACTR-33. INFIGRATINIB (BGJ398) IN PATIENTS WITH RECURRENT GLIOMAS WITH FIBROBLAST GROWTH FACTOR RECEPTOR (FGFR) ALTERATIONS: A MULTICENTER PHASE II STUDY. (11th November 2019) - Lassman, Andrew; Sepúlveda-Sánchez, Juan; Cloughesy, Timothy; Gil-Gil, Juan; Puduvalli, Vinay; Raizer, Jeffrey; De Vos, Filip; Wen, Patrick; Butowski, Nicholas; Clement, Paul; Groves, Morris; Belda-Iniesta, Cristobal; et al.
Abstract: INTRODUCTION: FGFR mutations and translocations occur in approximately 10% of glioblastomas (GBMs). FGFR3-TACC3 fusion is predictive of response to FGFR tyrosine kinase inhibitors pre-clinically and clinically. Infigratinib (BGJ398) is a selective small-molecule pan-FGFR kinase inhibitor with anti-tumor activity in several solid tumors with FGFR genetic alterations. METHODS: Open-label phase II trial of adults with recurrent high-grade gliomas following failure of initial therapy (NCT01975701). Tumors harbored FGFR1-TACC1 or FGFR3-TACC3 fusions, activating mutations in FGFR1, 2 or 3, or FGFR1, 2, 3, or 4 amplification. Oral infigratinib was administered 125 mg d1–21 q28d. Prophylaxis for hyperphosphatemia was recommended. Primary endpoint: 6-month progression-free survival (6mPFS) rate by RANO (locally assessed); goal of >40%. RESULTS: As of Sep 2017, 26 patients (16 men, 10 women; median age 55 years, range 20–76 years; 50% with ≥ 2 prior regimens) were treated; 24 (92.3%) discontinued for disease progression (n=21) or other reasons (n=3). All had FGFR1 or FGFR3 gene alterations; 4 had >1 gene alteration. Estimated 6mPFS rate was 16% (95% CI 5.0–32.5%); median PFS was 1.7 months (95% CI 1.1–2.8 months); median OS was 6.7 months (95% CI 4.2–11.7 months); ORR was 7.7% (95% CI 1.0–25.1%). Best overall response was: partial response 7.7% (FGFR1 mutation n=1; FGFR3 amplification n=1); stable disease 26.9%; progressive disease 50.0%; missing/unknown 15.3%. Most common (>15%) all-grade treatment-related adverse events (AEs) were hyperphosphatemia, fatigue, diarrhea, hyperlipasemia, and stomatitis. There were no grade 4 treatment-related AEs. Eleven patients (42.3%) had treatment-related AEs requiring dose interruptions/reductions (most commonly hyperphosphatemia). CONCLUSIONS: Infigratinib induced partial response or stable disease in approximately one-third of patients with recurrent GBM and/or other glioma subtypes harboring FGFR alterations. Most AEs were reversible and manageable. Further potential combinations are being explored in patients with proven FGFR-TACC fusion genes; analysis of biomarker data is ongoing.